Analisis Penerapan Keselamatan Dan Kesehatan Kerja (K3) Dalam Meminimalisir Resiko Kerja Pada CV. Cipta Karya Mandiri - I Dewa Gede Darma Putra Suryawan; Dodit Cahyo Nugroho (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2025)
To minimize the risk of accidents and improve work safety in the work environment, every shipping company is required to follow the applicable regulations in accordance with the rules made by officials or related institutions that have the authority over it. The purpose of this study is to determine the extent to which the implementation of the K3 Management System is applied in the company CV. Cipta Karya Mandiri to improve work safety. Thus it is expected that the risk of accidents and occupational health can be minimized by the company so as not to cause losses and fatalities. In analyzing and describing the Implementation of the Occupational Health and Safety System (SMK3) to reduce the risk of work accidents at CV. Cipta Karya Mandiri This study uses qualitative research where the theoretical basis is a guide so that the focus of the research is in accordance with the facts in the field. The place of research was conducted at CV. Cipta Karya Mandiri where the Company has stated its commitment even though it has not been written, the K3 organization has not been formed, conducting K3 counseling to workers, implementing K3 programs such as providing PPE, health checks, and treating sick workers by providing BPJS services. Although the implementation of monitoring and evaluation has not been running. A written commitment is needed to implement K3 at CV. Cipta Karya Mandiri and immediately form an OHS organization with responsibilities and functions that can be carried out properly to reduce occupational diseases and accidents, it is expected to be an assessment of occupational safety and a reference for a health management system, and can continue to study and analyze the occupational safety and health management system of CV. Cipta Karya Mandiri.